Balance training reduces postural sway and improves sport-specific performance in visually impaired cross-country skiers - Kurz, A.; Lauber, B.; Franke, S.; Leukel, C. (The Journal of Strength and Conditioning Research, 2021)
Balance training is highly effective in reducing sport injuries and causes improvements in postural stability and rapid force production. So far, the positive effects of balance training have been described for healthy athletes. In the present experiments, we questioned whether athletes with disabilities of the visual system can also benefit from balance training. Fourteen visually impaired cross-country skiers participated in this randomized controlled study. The intervention group (N = 7) completed 8 sessions of balance training over a period of 4 weeks (2 times per week), whereas a waiting control group (N = 7) received no training during that time. After training, postural sway was significantly reduced in the intervention group but not in the waiting control group. In addition, sport-specific performance, which was assessed by a standardized Cooper's 12-minute test on roller skis or rollerblades, increased in the intervention group. The change in postural sway from the premeasurement to the postmeasurement correlated with the change in sport-specific performance in all subjects. Our results indicate that balance training is useful for improving postural stability and sport-specific performance in visually impaired cross-country skiers. We propose that balance training should therefore be implemented as part of the training routine in athletes with disabilities of the visual system.